Contextual Digital Word Cards for Letter Recognition in Early Readers: Kartu Kata Digital Kontekstual untuk Pengenalan Huruf pada Pembaca Pemula - Suprapti, Endang; Purwanta, Edi (Indonesian Journal of Innovation Studies, 2025)
Background: Reading ability is a crucial foundation for children’s academic success, and many second-grade students still struggle with letter recognition and writing basic words. Specific Background: Traditional teaching media are often monotonous and fail to sustain student motivation, resulting in low literacy achievement. Knowledge Gap: Few studies explore contextual digital word cards as a medium tailored to early readers with reading difficulties. Aim: This study aimed to examine the use of contextual digital word cards to support letter recognition in second-grade students. Results: Using a classroom action research design with two cycles, involving 15 students, results showed a steady rise in mastery: 26.67% (pre-cycle), 62.49% (cycle I), and 71.67% (cycle II). Students demonstrated greater motivation, accuracy in identifying letters, and improved writing performance. Novelty: This study integrates digital media with contextual vocabulary to create an engaging and interactive literacy learning environment. Implications: Teachers are encouraged to adopt contextual digital word cards as an innovative approach to build early reading readiness and foster active classroom participation. Highlight: Students showed steady improvement in letter recognition and writing skills Contextual digital word cards increased engagement and participation Two learning cycles met class-level mastery target Keyword: Letter Recognition, Early Reading, Contextual Learning, Digital Word Cards, Classroom Action Research